ANALISIS PENGGUNAAN METODE TAHFIDZ AL-QURAN DALAM MENGEMBANGKAN NILAI AGAMA DAN MORAL ANAK USIA 5-6 TAHUN DI PAUD ROUDLOTUL QURAN DESA CICAPAR - Lastari, Lastari; Hidayat, Rahmat (Jurnal Intisabi, 2024)
Al-Quran tahfidz method is appropriate used in developing religious and moral values to early childhoods. The aim of this study is to find out how the implementation of al-Quran tahfidz method on the development of religious and moral values to early childhoods aged 5-6 years at PAUD Roudlotul Quran Cicapar Village. This study used a qualitative method under a descriptive approach. Then, the results of the study showed that al-Quran tahfidz method is appropriate to develop religious and moral values to early childhoods aged 5-6 years, such as: (1) early childhoods are able to recite short prayers, such as: prayers before and after learning, (2) early childhoods have good manners to their teachers, parents and classmates, (3) early childhoods have a humble attitude to their teachers and classmates, (4) early childhoods know the daily worship activities, (5) Al-Quran tahfidz method supports early childhood to create good communication among their classmates, and (6) early childhoods have a sense of responsibility for the tasks given. In conclusion, al-Quran tahfidz method is one of the appropriate methods to instill and develop religious and moral values to early childhoods aged 5-6 years in PAUD Roudlotul Quran Cicapar Village.